2015
DOI: 10.1667/rr14222.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proton and Combined Proton and 56Fe Radiation on the Hippocampus

Abstract: The space radiation environment contains protons and (56)Fe, which could pose a significant hazard to space flight crews during and after missions. The space environment involves complex radiation exposures, thus, the effects of a dose of protons might be modulated by a dose of heavy-ion radiation. The brain, and particularly the hippocampus, may be susceptible to space radiation-induced changes. In this study, we first determined the dose-response effect of proton radiation (150 MeV) on hippocampus-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 49 publications
3
68
0
Order By: Relevance
“…Only a few studies have examined CFC in young adult mice after HZE-particle exposure, and it is challenging to compare these to our work. For example, young adult mice exposed to protons (150 MeV) have shown increased freezing at low dose (0.1 Gy) with no change at higher doses (0.5, 1 Gy) at 1 month postirradiation, and no change in any group at 3 months postirradiation (27). However, cued FC was not reported as being assessed, so it remains possible that increased freezing at 0.1 Gy proton irradiation was due to anxiety, not improved memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have examined CFC in young adult mice after HZE-particle exposure, and it is challenging to compare these to our work. For example, young adult mice exposed to protons (150 MeV) have shown increased freezing at low dose (0.1 Gy) with no change at higher doses (0.5, 1 Gy) at 1 month postirradiation, and no change in any group at 3 months postirradiation (27). However, cued FC was not reported as being assessed, so it remains possible that increased freezing at 0.1 Gy proton irradiation was due to anxiety, not improved memory.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to answer this question is to widen the comparison to all studies investigating HZE-induced behavioral changes in young adult mice after exposure to mission-relevant doses (<1 Gy and ideally <0.2 Gy). From this perspective, there is increasing evidence that lower doses of 56 Fe (as low as 0.2 Gy), 28 Si (0.005 Gy), 16 O (0.01 Gy), 12 C (0.05 Gy), protons (0.1 Gy) or combined exposure (e.g., protons and 56 Fe) impede hippocampal, striatal and executive function in young adult rats and mice (9, 27, 91100) in an energy-dependent manner. Although there is a relative paucity of behavioral studies using 28 Si radiation, our data show that exposure to 0.2 Gy 28 Si radiation induces deficits in hippocampal function even at 3 months postirradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham irradiated mice served as controls and were placed into the same enclosures and for the same amount of time, since previous studies reported no effect of sham irradiation on molecular end-points (Miousse et al, 2014). One week after irradiation, the mice were shipped to Oregon Health and Science University (OHSU) where they underwent behavioral testing reported elsewhere (Raber et al, 2015). Food (PicoLab Rodent Diet 20, no.…”
Section: Methodsmentioning
confidence: 99%
“…It is now recognised that sufficient doses of ionising radiation can induce microglial activation and pro-inflammatory derived factors which can propagate radiation-induced brain injury [90], [91]. Correspondingly, radiation-induced neuroinflammation can inhibit adult neurogenesis in the hippocampus [92], [93], [94], [95], with longer term cognitive deficits in patients persisting from months to decades after initial exposure [96]. Interestingly, the finding of reversible inhibition of the proliferative capacity of progenitor cells in the dentate gyrus 1 week after 4 Gy X-radiation exposure, with an absence of microglial activation [97], suggests there is a requirement of neuroinflammatory processes to cause persistent and deleterious effects to cells [98].…”
Section: The Impact Of High Dose Ionising Radiation On the Cnsmentioning
confidence: 99%